Stocktaking Management System - Dweikat, Ahmed; Dweikat, Taher (My University, 2017)
In the last few years, Palestine has witnessed a significant development in the commercial and industrial sector. This development makes an increasing growth in the size of the inventories that this sector has. This means an increasing number of the items that are stored in these inventories. The huge number of items requires more time and effort to manage these inventories and perform different operations on them. One of the operations that are considered important in managing the stocks is Stock Taking .Stock Taking or "inventory checking" is the physical verification of the quantities and condition of items held in an inventory or warehouse. The purpose of this project is to build an integrated Stock Taking System, for companies that have stocks and intend to perform the operation of stock taking on them.The plan is to help these companies gradually replace the paper-based stock taking process with a mobile and web applications, in order to reduce errors that may appear from paper work and to minimize the cost and time taken by the employees to finish this operation. By using this system the user will be able to define all the information related to inventories and the items stored in them such as the names, units, factory numbers and barcodes of these items. The user will also be able to view different system Reports, perform the operation of stock taking in multiple modes such as the manual and automatic barcode modes. In addition to University supervisors, this project has been supervised by “Isra’ Software and Computer Company”. Requirements have been gathered, analysed and discussed with the team before starting development process. In the development process, many tools have been used in order to build the web and mobile applications: • SQL Server 2008, SQL management Studio and Layer Generator for Database • Visual Studio 2012 for the web application code • DevExpress Tools [1] for main Components in the web application • Android Studio for mobile application